1992
DOI: 10.1103/physrevc.46.655
|View full text |Cite
|
Sign up to set email alerts
|

K+total cross sections onC12

Abstract: The total cross sections for K+ mesons on carbon and deuterium nuclei have been measured at eleven momenta in the range 450-740 MeV/c. The experimental technique was of the standard transmission type. The K+ meson is the least strongly interacting of available hadronic probes, with a long mean free path in nuclear matter. At low incident momentum the K+K interaction is dominated by the Szz phase shift and varies slowly with energy. These characteristics make the K+ an ideal tool for probing the nuclear volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 29 publications
3
43
2
Order By: Relevance
“…Total cross sections for K + -nucleus have been extracted from transmission experiments [2,3,4]. Such data are complementary to the differential cross section data and exhibit often larger differences among the full-folding and tρ results, even though the same KN effective interaction is used.…”
Section: Applications and Resultsmentioning
confidence: 99%
“…Total cross sections for K + -nucleus have been extracted from transmission experiments [2,3,4]. Such data are complementary to the differential cross section data and exhibit often larger differences among the full-folding and tρ results, even though the same KN effective interaction is used.…”
Section: Applications and Resultsmentioning
confidence: 99%
“…(3) (lower part) the dependence on the beam momentum is reproduced at the level of 2-3% as is also the absolute scale of the cross sections. Including corrections due to Pauli correlations made no difference in the case of 6 Li, presumably because of the low density of this nucleus. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing total cross sections of K + on 6 Li with three times the cross sections on deuteron, it was found that within 2% there are no indications for medium effects in the results for 6 Li, where the average density is about half of the average density for other nuclei [10,11]. Consequently in what follows we use 6 Li as a reference. Ratios between experimental and calculated reaction (left panels) and total cross sections (right panels) of K + on C, Si Ans Ca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations